Periprocedural myocardial infarction is associated with increased mortality in patients with coronary artery bifurcation lesions after implantation of a drug‐eluting stent. Issue 1 (March 2015) - Chen, Shao‐Liang; Zhang, Jun‐Jie; Ye, Fei; Tian, Nai‐Liang; Sheiban, Imad; Jepson, Nigel; Paiboon, Chitprapai; Sansoto, Teugh; Kwan, Tak W.; Wen, Shang‐Yu; Wang, Hai‐Chang; Jiang, Tie‐Ming; et al.
<x xml:space="preserve">Abstract</x> Objectives The present study aimed to investigate the association between periprocedural myocardial infarction (PMI), defined by creatine kinase (CK)‐MB or troponin I (TNI) level elevations >5 times the 99th percentile of the upper reference limit (URL) within 48 hr after implantation of a drug‐eluting stent (DES), and one‐year mortality in patients with coronary bifurcation. Background PMI is reported to be associated with increased one‐year mortality after DES implantation. However, the prevalence and association of PMI with mortality after stenting bifurcation lesions remains unclear. Methods We prospectively followed 1, 971 patients with true coronary bifurcations who underwent DES implantation as part of the multicenter DEFINITION study. These patients were grouped into categories based on PMI outcome: Non‐PMI, CKMB‐PMI, TNI‐PMI, and CKMB/TNI‐PMI. The primary endpoint was the rate of all‐cause mortality at one year. Results PMI occurred in 11.4% of patients by CKMB criteria and 41.3% of patients by TNI criteria. At one‐year follow‐up, the mortality rate was 2.3% in the entire patient population. However, mortality was significantly higher in the CKMB‐PMI (6.4%) and CKMB/TNI‐PMI (6.1%) groups compared to the Non‐PMI (1.7%) and TNI‐PMI (2.1%) groups (all P < 0.05). A 10‐fold increase in TNI levels resulted in similar PMI rate (5.2%) and mortality risk (adjusted HR 2.7, 95% CI 3.0–5.2) as a fivefold increase in CKMB levels. Conclusions PMI, as defined by CKMB elevations following coronary bifurcation lesion stenting, was associated with increased one‐year mortality. Additionally, to attain an equal frequency of PMI, the elevation in TNI levels needed to be twice as high as the elevation in CKMB levels. © 2015 Wiley Periodicals, Inc.